Associations between cardiovascular disease risk factors and spinal pain may be moderated by sex and health-related physical activity (CHAMPS Study-DK) - Amber M. Beynon; Niels Wedderkopp; Charlotte Leboeuf-Yde; Jan Hartvigsen; Bruce F. Walker; Jeffrey J. Hébert (PLoS ONE, 2022)
Background Spinal pain has been previously linked with cardiovascular disease risk factors in children. This study investigated the prospective associations between cardiovascular disease risk factors and non-traumatic spinal pain occurrences in children, and examined the moderating role of sex and health-related physical activity in these relationships. Methods We used prospective data from the Childhood Health, Activity, and Motor Performance School Study Denmark (CHAMPS Study-DK). The exposure variables were a clustered cardiovascular risk score and homeostasis assessment model-estimated insulin resistance (HOMA-IR) score collected in 2008 and 2010. The spinal pain outcome comprised the number of weeks of non-traumatic spinal pain from 2008–2010 and 2010–2012. Potential confounders included age, sex, and time spent in moderate-to-vigorous intensity physical activity. We constructed age-adjusted mixed negative binominal regression models to investigate the prospective associations of cardiovascular disease risk factors and non-traumatic spinal pain, while considering the potential moderating roles of sex and physical activity in these relationships. Results Girls with low HOMA-IR scores and boys with low clustered cardiovascular disease risk scores, who engaged in higher levels of moderate-to-vigorous physical activity, reported more weeks of spinal pain, compared to girls with high HOMA-IR scores (p = 0.001) and boys with high clustered cardiovascular disease risk scores (p = 0.024). whereas boys with higher clustered cardiovascular disease risk who had less time in moderate-to-vigorous physical activity reported more weeks of spinal pain than boys with low clustered cardiovascular disease risk score (p = 0.024). Conclusion Our results show that cardiovascular disease risk factors are related to future occurrences of non-traumatic spinal pain. However, these relationships appear complex and dependent on the nature of the interactions with sex and physical activity.